2016
DOI: 10.3390/catal6070103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Method Using DMF as a Reducing Agent for the Fabrication of PdAg Nanochain Catalysts towards Ethanol Electrooxidation

Abstract: Abstract:In this article, we developed a facile one-step hydrothermal method using dimethyl formamide (DMF) as a reducing agent for the fabrication of PdAg catalyst. The scanning electron microscope (SEM) and transmission electron microscopy (TEM) images have shown that the as-synthesized PdAg catalyst had a nanochain structure. The energy-dispersive X-ray analyzer (EDX) spectrum presented the actual molar ratio of Pd and Ag in the PdAg alloy. Traditional electrochemical measurements, such as cyclic voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Commonly,t ypicald iffraction peaks related to Pd could be observed that is, at 39.78,4 5.28,6 7.38 and 80.88 corresponding to the (111), (200), (220) and (311) lattice planes. [77,78] Although, in case of the native Pd colloidal catalyst the (111)c ould be observed prominently while( 200), (220) and( 311) are less prominent. However, with the synthesized heterobimetallicPd/Ag colloid system ad efinite shift in the diffractionp eaks could be observed with the (111)l attice showing maximum shift.…”
Section: Scheme2oxidative Esterification With Different Alcoholic Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly,t ypicald iffraction peaks related to Pd could be observed that is, at 39.78,4 5.28,6 7.38 and 80.88 corresponding to the (111), (200), (220) and (311) lattice planes. [77,78] Although, in case of the native Pd colloidal catalyst the (111)c ould be observed prominently while( 200), (220) and( 311) are less prominent. However, with the synthesized heterobimetallicPd/Ag colloid system ad efinite shift in the diffractionp eaks could be observed with the (111)l attice showing maximum shift.…”
Section: Scheme2oxidative Esterification With Different Alcoholic Pamentioning
confidence: 99%
“…The structural features of the synthesized hetero‐bimetallic‐Pd/Ag colloids were characterized by subjecting the powder to XRD studies with the XRD profiles of the synthesized Pd/Ag overlaid onto the native Pd colloidal catalyst (Figure ). Commonly, typical diffraction peaks related to Pd could be observed that is, at 39.7°, 45.2°, 67.3° and 80.8° corresponding to the (111), (200), (220) and (311) lattice planes . Although, in case of the native Pd colloidal catalyst the (111) could be observed prominently while (200), (220) and (311) are less prominent.…”
Section: Figurementioning
confidence: 99%
“…In general, the Nyquist plot is related to the charge transfer resistance (R ct ) of the electrochemical reaction in high frequency region and Warburg impedance in low frequency zone. [43][44][45] Fig. 10 represents the Nyquist plots of the Au@Pd/ PMo 12 /rGO and Pd/PMo 12 /rGO to evaluate the kinetics of electrocatalyst in EOR.…”
Section: Eor Analysismentioning
confidence: 99%
“…Despite these advantages, less attention has been given to control the configuration, i.e., decorated or core-shell, of Pd coating on 1D Ag nanostructures and evaluate their EOR activities. Moreover, in order to synthesize PdAg nanostructures as a catalyst for EOR, current researches have operated at high Pd/Ag molar ratios from 1:3 to 1:1 [15,16,32,[40][41][42]. Meanwhile, it is informed that the Pt or Pd particles, which are inner the catalyst, show no contribution in the catalytic activities [43,44].…”
Section: Introductionmentioning
confidence: 99%